2011
DOI: 10.4253/wjge.v3.i11.213
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and retrograde cholangiographic appearance of hepaticojejunostomy strictures: A practical classification

Abstract: AIM:To study the endoscopic and radiological characteristics of patients with hepaticojejunostomy (HJ) and propose a practical HJ stricture classification. METHODS:In a retrospective observational study, a balloon-assisted enteroscopy (BAE)-endoscopic retrograde cholangiography was performed 44 times in 32 patients with surgically-altered gastrointestinal (GI) anatomy. BAE-endoscopic retrograde cholangio pancreatography (ERCP) was performed 23 times in 18 patients with HJ. The HJ was carefully studied with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, all 3 patients with hepaticojejunostomies could be classified as having a type A1 hepaticojejunostomy. 19 (3) The study lacked a direct comparison with other methods of deep enteroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all 3 patients with hepaticojejunostomies could be classified as having a type A1 hepaticojejunostomy. 19 (3) The study lacked a direct comparison with other methods of deep enteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopic-radiologic classification of hepaticojejunostomy strictures has been recently proposed by Mönkemüller and Jovanovic. 19 This classification and data regarding the appearance of the hepaticojejunostomies were not originally included in our prospective study because that classification was not available at the time. However, all 3 patients with hepaticojejunostomies could be classified as having a type A1 hepaticojejunostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported success rates in patients who undergo reoperation for biliary-enteric anastomosis either after pancreatic surgery or bile duct injury, 7,8 however, endoscopic and percutaneous interventions are coming to the forefront. 911 While the need for repeat procedures with attendant morbidity may be expected, the incidence of these procedures remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Locating the choledochojejunal anastomosis was difficult, but was successfully achieved by detecting the ulcer-scar-like lesion and a little biliary flow in the underwater observation (• " Video 1). However, the procedure failed because of a severe stenosis consisting of a long stricture with a small orifice in the choledochojejunal anastomosis, which was denoted a type A2 stricture in the classification of Mönke-müller and Jovanovic [1] and hindered the advancement of several devices. As an alternative, percutaneous transhepatic cholangiodrainage (PTCD) was applied, but this was again precluded by the severe stenosis.…”
mentioning
confidence: 99%